FEEDBACKINSIGHT-AI: A SYSTEM FOR TRIAGE, CLASSIFICATION, AND SUMMARIZATION OF CUSTOMER FEEDBACK USING ARTIFICIAL INTELLIGENCE - Magalhães, Filipe; Marques, Matheus; dos Santos, Ricardo Marciano; Boente, Alfredo Nazareno Pereira; Ferreira, Vinícius Marques da Silva; de Carvalho, Miguel Gabriel P.; da Conceição, Thiago Silva; Almeida, Rosangela de Sena (Seven Editora, 2025)
This article proposes FeedbackInsight-AI, an automated system for triaging, classifying, and summarizing customer feedback using Artificial Intelligence (AI) and Natural Language Processing (NLP) techniques. The objective is to optimize the handling of large volumes of messages received by companies, reducing response time and enabling more efficient information analysis. The study is based on a qualitative and descriptive approach, using machine learning models applied to sentiment analysis and text categorization. The methodology involves integration between communication (Gmail), management (Trello), and data analysis (Google Sheets) APIs, utilizing state-of-the-art language models (like GPT-4). The proposal aims to contribute to the advancement of intelligent automation in customer service processes and data-driven decision-making in organizations. DOI: https://doi.org/10.56238/sevened2025.036-074